Alteration of Tissue Marking Dyes Depends on Used Chromogen during Immunohistochemistry - Kiefer, Selina (Cells, 2021)
Pathological biopsy protocols require tissue marking dye (TMD) for orientation. In some cases (e.g., close margin), additional immunohistochemical analyses can be necessary. Therefore, the correlation between the applied TMD during macroscopy and the examined TMD during microscopy is crucial for the correct orientation, the residual tumour status and the subsequent therapeutic regime. In this context, our group observed colour changes during routine immunohistochemistry. Tissue specimens were marked with various TMD and processed by two different methods. TMD (blue, red, black, yellow and green) obtained from three different providers (A, B and C, and Whiteout/Tipp-Ex(®)) were used. Immunohistochemistry was performed manually via stepwise omission of reagents to identify the colour changing mechanism. Blue colour from provider A changed during immunohistochemistry into black, when 3,3′-Diaminobenzidine-tetrahydrochloride-dihydrate (DAB) and H(2)O(2) was applied as an immunoperoxidase-based terminal colour signal. No other applied reagents, nor tissue texture or processing showed any influence on the colour. The remaining colours from provider A and the other colours did not show any changes during immunohistochemistry. Our results demonstrate an interesting and important pitfall in routine immunohistochemistry-based diagnostics that pathologists should be aware of. Furthermore, the chemical rationale behind the observed misleading colour change is discussed.